A critical analysis of the General Anti‐avoidance rules as envisaged in sections 80A‐80L of the Income Tax Act 58 of 1962 - Ngcobo, Matshidiso (University of the Witswatersrand, Johannesburg, 2021)
The general anti‐avoidance provisions commonly known as general anti‐avoidance rules or “GAAR” exist in many jurisdictions around the world. Tax authorities, lawmakers and other stakeholders (such as the Organisation for Economic Co‐operation and Development (OECD)) around the world introduced and continuously develop the anti‐avoidance rules applicable in their respective jurisdictions. The purpose of this report is to critically analyse the general anti‐avoidance provisions in their old form (i.e. section 103(1) of the Income Tax Act prior to its repeal) and the current form (i.e. sections 80A to 80L of the Income Tax Act) in order to assess whether the current provisions are achieving the objective of protecting the fiscus against the non‐payment/delayed payment of tax. This report will also analyse the Australian general anti‐avoidance rules. Such provisions or rules serve to protect a country’s tax base or the fiscus from transaction(s) entered by taxpayers for the sole or main reason of obtaining a tax benefit. Anti‐avoidance provisions aim at identifying these transactions and reversing whatever tax benefit that might have been derived from the transaction where such transaction(s) were entered into for the sole or main reason of obtaining the tax benefit.
“A research report submitted to the Faculty of Commerce, Law and Management in partial fulfilment of the requirements for the degree of Master of Commerce specialising in Taxation”.
Keywords: UCTD; Avoidance arrangement; Tax benefit; General anti‐avoidance rules; GAAR; Impermissible avoidance arrangement; Australia; Tax avoidance; SDG-8: Decent work and economic growth